Adapting to the New Transformation of the Economy - Mulas, Victor (World Bank, Washington, DC, 2017)
Increasing signs suggest that the economy is in the process of a significant restructuring process. Technology-led transformations are no longer limited to technology-related sectors and are beginning to impact structural sectors, including manufacturing, retailing, transportation, and construction. This change has potentially significant implications for the competitiveness of countries, business, and people. Some countries are starting to react to these economic changes in order to maintain their competitiveness. Most of these countries, however, are developed countries. If emerging economies want to remain competitive, they will also need to adapt to these economic trends. This paper presents policy areas for countries to prepare these economies to technology changes in order to maintain competitiveness and the creation of employment and growth.